Parâmetros genéticos para características indicadoras de eficiência reprodutiva e produtiva de ovinos da raça Santa Inês - Ono, Rafael Keith [UNESP] (2015)
Reproductive efficiency traits are of significant economic importance as they relate to the source income of sheep meat enterprise. Reliable genetic parameters are essential for selection index design and to determine the correlated response to selection that will occur in other traits in a selection index. Thus, the aim of this study was to estimate (co)variance components and parameter genetics for reproductive traits in Santa Inês sheep. Data included records of 4,742 Santa Inês sheep from Santa Inês Breeding Program of Sergipe State Sheep and Goats Breeders Association and University of São Paulo. In the first part, studied traits were age at first lambing (AFL), Lambing Interval (LI), Litter size at birth per ewe lambing(LSB), Litter size at weaning per ewe lambing and Ewe rearing ability per ewe lambing (RA) defined as lambs weaned per lamb born. The (co)variance components were estimated by bivariate analysis using Gibbs sampling methodology with THRGIBBS1F90 software and number of iterations, length of burn-in and sampling interval were 1,500,000, 500,000 and 250, respectively. For AFL and LI, a linear model was applied and for LSB, LSW and RA, a threshold model. Posterior means of heritability were 0.239 ± 0.053 for AFL, 0.056 ± 0.022 for LI, 0.098 ± 0.047 for LSB, 0.016 ± 0.01 for LSW and 0.019 ± 0.011 for RA. Posterior means of genetic correlation among reproductive traits ranged from -0.62 between LSB and RA to 0,82 between LSW and RA. Posterior means of phenotypic correlation between AFL and LI and each one among the others were low, close to zero. The phenotypic correlation were positive and medium between LSB and LSW (0.44 ± 0.02), medium and negative between LSB and RA (0.37 ± 0.02) and were high and positive between LSW and RA (0.98 ± 0.00). Reasonable genetic progress can be obtained in sexual precocity using age at first lambing as selection criteria. Large influences of environmental effects on LI, LSB ...